Deciphering the 'othering' of Muslims - Ahmad Farouk, Azeem Fazwan (New Straits Times Press (M) Berhad, 2016)
THE predominant Western view on Islam is very much informed by the orientalist discourse. In order to understand the “othering” of Muslims, we have to go back several centuries and situate the present state of affairs within the Western global/colonial designs.